Memahami Arti Penting Mars HIMPAUDI - Said Said; Indayati Indayati; Rosul Rosul (STAI Publisistik Thawalib Jakarta, 2022)
Early childhood education in Indonesia is gathered in one organization called Himpaudi. The function of the organization is to maintain the quality and credibility of early childhood learning so that it is in accordance with the development and age of the child. Himpaudi has a march that has many important meanings, one of which is (1) that early childhood education is accommodated by an early childhood education institution that functions as a place for children to be creative. (2) educators in early childhood education institutions are obliged to carry out education with joy and a radiant face. (3) Early childhood education institutions must organize education by forming the character of early childhood who are honest, friendly and always want to try. Thus, the existence of early childhood education institutions is able to form early childhood who are religious and have good morals and social spirit.